Anti-thyroglobulin Antibodies as a Possible Risk Factor for Graves' Disease After Radioiodine Treatment for Toxic Nodular Goiter: Case Report - Rouiller, Nathalie; Nicod Lalonde, Marie; Sykiotis, Gerasimos P. (Frontiers in Nuclear Medicine, 2022)
Background The manifestation of Graves' disease (GD) in patients treated with radioactive iodine (RAI) for hyperfunctioning thyroid nodules (RAI-induced GD or post-RAI GD) remains a long-standing challenge in radionuclide therapy. Known risk factors for post-RAI GD include preexisting subclinical hyperthyroidism, positive thyroid peroxidase autoantibodies (TPOAb), positive TSH receptor autoantibodies (TRAb) or otherwise undiagnosed GD. However, these risk factors are not present in all patients with post-RAI GD, and therefore it cannot always be predicted in a reliable manner if a given patient has a high risk for RAI-induced GD or not. Case Presentation We describe the case of a 64 year-old woman known for hyperthyroidism due to toxic nodular goiter; she was treated initially with carbimazole, and then, due to recurrence, underwent RAI treatment. Three months later, symptomatic hyperthyroidism persisted. Diagnosis of new-onset GD was made based on typical ultrasound findings and newly-positive TRAb. Our patient had only positive thyroglobulin antibodies (TgAb) before RAI treatment, whereas TPOAb were negative. Conclusions In the literature, TgAb have never been reported as a possible risk factor for RAI-induced GD. The present case suggests that the assessment for pre-existing autoimmunity in patients considering RAI for hyperfunctioning thyroid nodules should probably also include TgAb.